Carbon footprint of wooden and plastic pallets: A quantification with different software tools - Vásquez, Marcia; Vásquez, Leonardo; Musule, Ricardo; Iriarte, Alfredo (Maderas. Ciencia y Tecnología, 2022)
Transport is one of the activities that generates the highest CO2eq emissions. In the particular case of Chile, it is the second economic activity that generates the greatest environmental impact. The safe and efficient transport of products in domestic and foreign markets is often carried out with the help of pallets made of various materials, such as wood or plastic, which goes hand in hand with different environmental performance in their production. That is why it is important to know the carbon footprint of these products. The objectives of this study are to compare the value of the carbon footprint generated by the local production of wooden and plastic pallets and to evaluate the variations in its quantification using different software. For this purpose, the Chilean market is taken as a reference. This study follows the main guidelines of ISO 14040 and ISO 14067 standards as a reference framework. The functional unit is 1 pallet produced and the system boundary is from cradle to gate. The results show that wood and plastic pallets have an average carbon footprint of 4,12 kg CO2eq and 38,85 kg CO2eq respectively. The difference between the two pallets is mainly due to the environmental load of the raw materials. The causes of the variation in the estimation of the carbon footprint with different software are specifically based on the databases with which they can work. The ratio of 1:9 between the carbon footprint of wooden pallets concerning plastic pallets provides important data for decision making.